Deterrents to Collaboration in the Provision and Regulation of Cross-Border Higher Education in East Africa - Sanga, Philipo Lonati (Papers in Education and Development, 2020)
Currently, many nations consider cross-border higher education (CBHE) as an effective strategy for providing higher education opportunities to all regardless of national boundaries, at a relatively low cost, and without irrationally compromising quality. Despite the nations being aware of the benefits of CBHE, there is still little evidence of significant collaborations among East African countries in this aspect. Accordingly, this paper interrogates the deterrents to collaboration in CBHE and their implications for sustainable higher education in the region. Besides the differences existing among East African countries, the paper suggests that countries and higher education institutions, in particular, should, inter alia, promote regional synergistic approaches for the provision and regulation of cross-border higher education to gain a prerequisite momentum for global competition. Keywords: collaboration in cross-border higher education, East African higher education mobility, regulation of cross-border higher education